1995
DOI: 10.1128/aac.39.4.910
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of SM-17466, a novel carbapenem antibiotic with potent activity against methicillin-resistant Staphylococcus aureus

Abstract: The in vitro and in vivo antibacterial activities of SM-17466, a new 1␤-methyl carbapenem, were evaluated against a wide range of clinical bacterial isolates and compared with the activities of meropenem, imipenem, vancomycin, and arbekacin. SM-17466 had a broad spectrum of action against gram-positive bacteria, showing especially potent activity against methicillin-resistant staphylococci. The MICs of SM-17466, meropenem, imipenem, vancomycin, and arbekacin at which 90% of clinical isolates of methicillin-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…The beta-lactam antibiotics that are used clinically do not bind to PBP 2a at therapeutic concentrations and therefore lack efficacy against infections caused by methicillin-resistant staphylococci. With the solution of the crystal structure of a soluble derivative of PBP 2a, low-affinity binding can be attributed at least in part to an energetically unfavorable acylation reaction of the active site serine due to the slippage of the beta-lactam molecule within a long groove that serves as the initial, reversible binding site in the formation of the Michaelis-Menten complex (16).Several cephalosporin and carbapenem derivatives that bind to PBP 2a with 100-fold or higher affinities than those of other beta-lactams and which are active in vitro and in vivo against methicillin-resistant staphylococci have been synthesized (2,6,7,13,20). These compounds have in common a relatively extended side chain attached to the ␣ ring of the beta-lactam compound core (3, 16).…”
mentioning
confidence: 99%
“…The beta-lactam antibiotics that are used clinically do not bind to PBP 2a at therapeutic concentrations and therefore lack efficacy against infections caused by methicillin-resistant staphylococci. With the solution of the crystal structure of a soluble derivative of PBP 2a, low-affinity binding can be attributed at least in part to an energetically unfavorable acylation reaction of the active site serine due to the slippage of the beta-lactam molecule within a long groove that serves as the initial, reversible binding site in the formation of the Michaelis-Menten complex (16).Several cephalosporin and carbapenem derivatives that bind to PBP 2a with 100-fold or higher affinities than those of other beta-lactams and which are active in vitro and in vivo against methicillin-resistant staphylococci have been synthesized (2,6,7,13,20). These compounds have in common a relatively extended side chain attached to the ␣ ring of the beta-lactam compound core (3, 16).…”
mentioning
confidence: 99%
“…Although drugs such as moxifloxacin, gatifloxacin and gemifloxacin have enhanced activity against staphylococci and MRSA (MIC 90 , 0.5 to 8.0 µg/mL) (55-58), there have been no published reports describing the use of these agents for the treatment of MRSA infections. Currently available fluoroquinolones are not recommended for the treatment of MRSA infections.…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…New carbapenems (eg, L-695,256 and SM-17466) able to bind to PBP 2a with a high degree of affinity have also been developed. These drugs appear to be active in vitro against MRSA strains (89,90) and L-695,256 appears to be as effective as vancomycin in an animal model of endocarditis (89).…”
Section: Investigational Compoundsmentioning
confidence: 99%
“…Several problems, however, such as the spread of teicoplanin-and arbekacin-resistant MRSA4) and the current emergence of glycopeptideintermediate S. aureus (GISA)5) are certainly reducing the efficacy of these drugs in the clinic. VRE were first reported in 1986, and identified with increasing frequency in many nations over the past 10 years6 26). However, it was found that the activity against VREFm was insufficient to allow for useful in vivo efficacy.…”
mentioning
confidence: 99%